2017
DOI: 10.1002/ps.4556
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vivo fungicidal activity of some new quinoline derivatives against rice blast

Abstract: Quinoline derivatives, especially benzyl (2,3,8-trimethyl-6-(perfluoropropan-2-yl)quinolin-4-yl) carbonate, which possess good control effective against rice blast and cucumber powdery mildew, may become new lead compounds for the development of fungicides with further structure modification. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…In our previous work , we found the perfluoropropanyl group on the quinoline ring can increase the fungicidal activity, so in line with our continued efforts to synthesize novel lead compounds for drug discover , the fungicide tebufloquin was selected as a lead compound, the t ‐Bu group was replaced by perfluoropropanyl group, and the fluorine atom was replaced by hydrogen atom. Then, the ether group was replaced by ester carbonate.…”
Section: Introductionmentioning
confidence: 95%
“…In our previous work , we found the perfluoropropanyl group on the quinoline ring can increase the fungicidal activity, so in line with our continued efforts to synthesize novel lead compounds for drug discover , the fungicide tebufloquin was selected as a lead compound, the t ‐Bu group was replaced by perfluoropropanyl group, and the fluorine atom was replaced by hydrogen atom. Then, the ether group was replaced by ester carbonate.…”
Section: Introductionmentioning
confidence: 95%
“…In our previous work, many heterocyclic derivatives were synthesized and their pesticidal activity was explored, in particular, the pyrazole ring with insecticidal, fungicidal, and nematocidal activity . The three types of pyrazole compounds were designed by extending the carbon chain between the acyl amide group and the benzene ring to discover highly active fungicidal lead compounds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In recent reference, her group 17 built a modelling of the P. capsici cellulose synthase 3. In our previous work [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , many bioactive compounds were designed and synthesised. In this paper, based on the structure of seven commercialised CAA fungicides, we found that they have similar structural fragments: amide bond, para-substituted phenyl, 3,4-dialkyloxy substituted phenyl.…”
Section: Introductionmentioning
confidence: 99%